2022
DOI: 10.1111/jfbc.14402
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Polygonatum sibiricum ameliorates glucose and lipid metabolism via PI3K / AKT signaling pathway in high‐fat diet and streptozotocin‐induced diabetic mice

Abstract: This study was aimed to investigate the protective effects and elucidate the mechanisms of aqueous extract of Polygonatum sibiricum (PSAE) on glucolipid metabolism during the development of type 2 diabetes (T2DM). C57BL/6J mice fed with 60% high‐fat diet (HFD) combined with streptozotocin (STZ) injection to simulate the occurrence process of T2DM. PSAE was administered daily by oral gavage during the experiment. The results demonstrated the protective effects in mice supplied with PSAE on the indicators of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Many studies have shown that interfering with PI3K/Akt and other pathways can result in hypoglycemic efects [39,40]. By activating the PI3K/AKT signaling pathway, the aqueous extract of Flos Aureus is also able to improve hepatic insulin resistance in mice [41]. Extracts from a variety of plants, such as white buttercup and Acanthopanax, have also been shown to afect glycolipid metabolism in mice by this pathway [18,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that interfering with PI3K/Akt and other pathways can result in hypoglycemic efects [39,40]. By activating the PI3K/AKT signaling pathway, the aqueous extract of Flos Aureus is also able to improve hepatic insulin resistance in mice [41]. Extracts from a variety of plants, such as white buttercup and Acanthopanax, have also been shown to afect glycolipid metabolism in mice by this pathway [18,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In studies based on hyperlipidemic and obese mouse models, Thujaplicins reduced the expression levels of SREBPs and PPARα and exerted regulatory lipid metabolism and antiinflammatory effects through activation of the AMPK signaling pathway [122,123]. In studies based on T2DM mice, Thujaplicins and aqueous extracts of C. tigris reduced blood glucose levels and blood lipid levels in mice, and Thujaplicins also repaired pancreatic β-cells to improve disorders of glucolipid metabolism [124,125].…”
Section: Reynoutria Japonica Houtt and Its Compounds Delay Cellular S...mentioning
confidence: 99%
“…Currently, clinical drugs for the treatment of diabetes may have certain side efects and their application is limited. More evidence shows that dietary modifcations can alleviate dyslipidemia and hyperglycemia to some extent [9,13], so the risk of developing T2DM and its complications can be reduced by consuming plants and their bioactive ingredients with efcacy and safety.…”
Section: Introductionmentioning
confidence: 99%